Correlates of perceived shared decision making with parents of children with special healthcare needs: Findings from the PART-CHILD study - Görig, Tatiana; Eichinger, Michael; Georg, Sabine; Hoffmann, Dorle; Philippi, Heike; König, Jochem; Urschitz, Michael Siegfried; Bock, Freia de (Patient education and counseling, 2024)
Objective - To assess the extent of perceived shared decision making (SDM) with parents of pediatric patients and to examine its association with characteristics of patients, professionals, and healthcare facilities. - Methods - Parents of pediatric patients (n = 4383) were recruited in 15 social pediatric centers in Germany and provided information on perceived SDM (binary CollaboRATEpediatric score: optimal versus suboptimal extent of SDM), child age and sex, type of impairment, appointment, and healthcare professional present at the appointment. Organizational characteristics were assessed in a cross-sectional survey of staff at the study sites. - Results - Overall, 58.4% of parents reported an optimal extent of SDM. The optimal extent of SDM was more likely reported by parents of girls (OR=1.27, p < 0.001) and children with physical (as opposed to cognitive and combined) impairments (OR=1.30, p = 0.006), and after appointments attended by allied health professionals (OR=1.28, p = 0.004). In addition, parents in facilities receiving financing in addition to compensation by statutory health insurance funds were less likely to report an optimal extent of perceived SDM. - Conclusion - While SDM with parents was mostly related to individual characteristics of children and professionals at appointments, organizational characteristics seemed less relevant in our study. - Practice implications - Staff should be made aware of lower SDM with parents of boys, older children, and those with cognitive impairments, and trained to improve the SDM in these groups.